Influence of play type on the magnitude and number of head impacts sustained in youth American football. Issue 11 (15th August 2022) - Vale, Adam; Post, Andrew; Cournoyer, Janie; Hoshizaki, T. Blaine; Gilchrist, Michael D.
Abstract: The magnitude and number of head impacts experienced by young American football players are associated with negative brain health outcomes and may be affected by play-type strategies. The purpose of this research was to examine how play type affects the magnitude and number of head impacts in youth American tackle football. Head impacts were recorded for 30 games in the 5–9 age category and 30 games in the 9–14 age category. Impacts using physical and finite element models were conducted to determine the brain strain. Run plays had a higher head impact frequency in both age groups ( p  < 0.05). This increase in head impacts was consistent for all positions ( p  < 0.05), except wide receiver, and offensive line and defensive back in the 9–14 age group ( p  > 0.05). Both age groups experienced significantly different magnitude proportions with higher numbers of very low and low strain magnitude impacts during run plays ( p  < 0.05), and a higher proportion of moderate magnitude impacts in the 5–9 age category ( p  < 0.05). This data can be used to inform and educate teams and coaches and influence decisions around the use of runs and passing plays that may lead to a decrease in head impacts.